Pengaruh Mobile Banking, Tingkat Pendidikan dan Tingkat Pendapatan Terhadap Perilaku Menabung Nasabah di Bank Nagari Kota Solok - Geri Trian Zetta; Ida Nirwana; Esi Sriyanti (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to analyze the effect of mobile banking, education level and income level on customer saving behavior at Bank Nagari Kota Solok. The sample in this study was 60 respondents who saved at Bank Nagari Kota Solok. Based on the results of the analysis that has been carried out, it is obtained that Y = 10,553 + 1.195X1 + 0.407X2 + 0.543X3 + e and t-test 9.805, 2.205, and 3.319, which means that the Mobile Banking variable affects the Savings Behavior of Customers at Bank Nagari Kota Solok, Education Level Variable affect the Saving Behavior of Customers at Bank Nagari Kota Solok and Income Level Variables affect the Saving Behavior of Customers at Bank Nagari Kota Solok. Judging from the value of R Square 0.650 which means that Mobile Banking, Education Level and Income Level have an effect of 65% on Customer Saving Behavior at Bank Nagari Kota Solok and 35% are influenced by other variables not examined in this study. From the analysis of the f-test the value of fcount is 34.611 > ftable 2.77 which means that mobile banking, education level and income level together affect the Savings Behavior of Customers at Bank Nagari Kota Solok.